METHODOLOGY OF USING GRAPHIC PROGRAMS FOR IMPROVING DESIGN THINKING OF FUTURE ENGINEERS-BUILDERS IN THE PROCESS OF GRAPHIC EDUCATION (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
in the process of graphic education at the institution of higher education, it is aimed at forming the graphic culture of future engineers-builders, as well as the creative potential of the individual. There are many effective works on this front, especially in the teaching of construction drawing, educational efficiency is achieved using modern graphic software. The BIM program is particularly perfect among the graphic programs for the field of architecture in explaining the topics of construction drawing, and it is an effective way to change the three-dimensional state of the drawings in front of the eyes of the students. For this reason, the use of graphic programs and their descriptions take a special place in elucidating the full essence of this science.